2014
DOI: 10.1002/ejic.201301473
|View full text |Cite
|
Sign up to set email alerts
|

Resorcinarenyl‐Phosphines in Suzuki–Miyaura Cross‐Coupling Reactions of Aryl Chlorides

Abstract: Two phosphines built on a bowl-shaped resorcin[4]arene skeleton, namely 5-diphenylphosphanyl-and 5-diisopropylphosphanyl-4(24),6(10),12 (16),18(22)-tetramethylenedioxy-2,8,14,20-tetrapentylresorcin[4]arene, have been synthesised and tested in the Suzuki-Miyaura cross-coupling reaction of aryl halides. Combining these ligands with [Pd(OAc) 2 ] resulted in highly active catalysts that allowed the formation of o,oЈ-biphenyls starting from aryl chlorides. The remarkable [a]1364 activities observed possibly arise f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…[8] The catalytic outcome contrasts with that observed for classical phosphino-enolato nickel complexes that do not contain an additional phosphine ligand, which typically result in long chain a-olefins under the above conditions. [9] Similar results were obtained when replacing NaBH 4 with NBu 4 BH 4 , thus excluding a cation effect. We tentatively propose that, after activation with borohydride, the borane formed binds the enolato oxygen atom of 6, thereby rendering the latter a weaker donor.…”
supporting
confidence: 84%
See 2 more Smart Citations
“…[8] The catalytic outcome contrasts with that observed for classical phosphino-enolato nickel complexes that do not contain an additional phosphine ligand, which typically result in long chain a-olefins under the above conditions. [9] Similar results were obtained when replacing NaBH 4 with NBu 4 BH 4 , thus excluding a cation effect. We tentatively propose that, after activation with borohydride, the borane formed binds the enolato oxygen atom of 6, thereby rendering the latter a weaker donor.…”
supporting
confidence: 84%
“…We have recently reported the synthesis of cavitand 1 , having a diphenylphosphino group grafted to its wider rim 4. The capacity of 1 to behave as a bulky, P‐monodentate ligand was demonstrated in the synthesis of several Pd II complexes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Elemental analyses were performed by the Service de Microanalyse, Institut de Chimie, Université de Strasbourg. 5,17‐Dibromo‐4(24),6(10),12(16),18(22)‐tetramethylenedioxy‐2,8,14,20‐tetrapentylresorcin[4]arene ( 1 )[10b] and 5‐diphenylphosphanyl‐4(24),6(10),12(16),18(22)‐tetramethylenedioxy‐2,8,14,20‐tetrapentylresorcin[4]arene were prepared by literature procedures.…”
Section: Methodsmentioning
confidence: 99%
“…A structural study combined with molecular modelling revealed that monophosphine 8 (Figure ), a cavitand with a P atom directly attached to the upper rim of the bowl, behaves as a ligand with variable bulk, its encumbrance depending on the orientation of the P lone pair . Thus, when the P atom points towards the cavitand axis, its cone angle is by ca.…”
Section: Catalytic Chemistry With Cavitands Substituted With P Donorsmentioning
confidence: 99%